Highly sensitive terahertz sensor for glucose detection - Kim, Hyo-Suk; Lee, Dong-Kyu; Seo, Minah; Chung, Youngchul; Lee, Seok (FIFTH ASIA-PACIFIC OPTICAL SENSORS CONFERENCE, 2015)
In this report, we present a new type of non-contact detection method for glucose molecule using nano antenna array based bio sensing chip that operates at terahertz frequency range (0.5 - 2.5 THz). Localized and hugely enhanced transmitted terahertz field by nano antenna array in the sensing chip induced enhancement of absorption coefficient of glucose molecule that enables us to detect even very small volume of molecules. Nano antenna based terahertz sensing chip can be expected to offer accurate identification of glucose level as a non-invasive and painless sensing tool with high sensitivity.